Application of continuous relative phase analysis for differentiation of gait in neurodegenerative disease. (May 2021) - Lukšys, Donatas; Jatužis, Dalius; Jonaitis, Gintaras; Griškevičius, Julius
Abstract: Continuous relative phase (CRP) is a measure of coordination between two joints, and CRP based analysis is being used to characterise joint or segmental coordination during gait. Postural instability or balancing issue is one of the major motor symptoms of Parkinson's Disease (PD). This study aimed to use CRP variables to distinguish between PD, healthy control (CO) groups, and PD groups divided according to clinical evaluations. The subjects were separated into two groups: healthy controls and Parkinson's disease subjects. Additionally, the PD group was subdivided according to the unified Parkinson disease rating scale (UPDRS) scores: UPDRS 0 and UPDRS 1. Each subject performed the designated walking motor task three times. Four inertial measurement units (IMU) were used to measure movement of the lower limbs. Statistically significant differences in CRP mean, deviation phase (DP), and root mean square CRP (CRPRMS ) were found for PD vs CO (right stance, right swing, right mid-stance) and UPDRS 0 vs UPDRS 1 (right stride, left stride, right swing). CRP can be used to separate PD and CO groups, and groups subdivided based on UPDRS score.